2010
DOI: 10.1007/s10995-010-0689-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Obesity in Childhood, Adolescence, and Adulthood in a Birth Cohort

Abstract: To determine how characteristics of pregnancy, birth, and early infancy are related to offspring obesity at three critical developmental periods. Mothers were followed through pregnancy and 10-15 years after. Offspring data were obtained through medical record review. Maternal and offspring characteristics were examined to predict obesity in childhood (ages 4-5 years), adolescence (ages 9-14 years), and early adulthood (ages 19-20 years). The original cohort included 802 children born to 795 women. Children wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
230
1
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(251 citation statements)
references
References 44 publications
15
230
1
5
Order By: Relevance
“…Some studies have assessed the association between low birth weight and the risk of childhood obesity, and the results are controversial 7,8,10,[12][13][14][15][16][17][18] Several studies have found that low birth weight was associated with a reduced risk of childhood obesity. 15,[17][18][19] However, other studies have indicated no association, 7,12,14 or an increased risk of obesity with low birth weight. 10,13 The present study was underpowered to identify any association between low birth weight and children obesity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Some studies have assessed the association between low birth weight and the risk of childhood obesity, and the results are controversial 7,8,10,[12][13][14][15][16][17][18] Several studies have found that low birth weight was associated with a reduced risk of childhood obesity. 15,[17][18][19] However, other studies have indicated no association, 7,12,14 or an increased risk of obesity with low birth weight. 10,13 The present study was underpowered to identify any association between low birth weight and children obesity.…”
Section: Discussionmentioning
confidence: 97%
“…Most past studies have found a significant and positive association between birth weight and childhood obesity risk. [7][8][9][10][11][12][13][14][15][16][17][18][19] A population-based cohort study from Denmark indicated an increased risk of overweight for children 6-13 years of age with birth weight ⩾ 4.0 kg compared with those with birth weight between 3.0 and 3.49 kg. 12 Another Chinese birth cohort found that children with higher birth weight ⩾ 3500 g had an increased odds of childhood overweight at 3-6 years of age compared with those having birth weight of 3000-3249 g. 15 A meta-analysis of 66 studies from 26 countries demonstrated that high birth weight (44000 g) was positively associated with increased odds of childhood overweight (OR 1.66; 95% CI: 1.55-1.77) compared with normal birth weight (2500-4000 g).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Importantly, the problem is transgenerational, with adverse effects on infant birthweight as well as childhood and adult obesity. 16 Over the last decade, the International Weight Management in Pregnancy (i-WIP) collaborative network, which is made up of 36 principal investigators from 17 countries, has evaluated various interventions based on diet and physical activity to improve clinical outcomes. 17 Collectively, experienced researchers, clinicians, nutritionists, dieticians, physiotherapists, exercise physiologists, midwives, nurses, and consumers in our field have come to the conclusion that to make substantive improvements to the health of the mother and future generations, the approach needs to be expanded beyond the gestational period.…”
mentioning
confidence: 99%
“…The present study reinforces the great deal of importance that has been focused on the influence of BMI and fat mass on motor performance tests. 10,26,34 These results can be confounded by other variables such as physical activity levels, for example.To study the associations among birthweight, body composition, and motor performance without overestimating the influence of birthweight and unduly selective emphasis on particular results, the present study used multiple linear regression models of increasing complexity. It was shown that the expectations of mean changes in the handgrip strength and 20-meter sprint time per 1g increase in birthweight in children are independent of current height, BMI, FFM, and % body fat.…”
mentioning
confidence: 99%